Effects of Cattle Manure or Its Combination with Chemical Fertilizers on Growing Celery Cabbage - Chanthan Or; Putheasath Sin; Chhun Hong; Vanchey Ros; Tithya Kang; Saroeun Kong; Dina Pen; Mardy Serey (Techno Agriculturae Studium of Research, 2024)
The experiment was conducted in Svay Rieng University in January and February 2015. The objective of the experiment was to test the effect of organic fertilizer from cattle manure alone or combination with inorganic fertilizer from urea and NPK on growing celery cabbage products. The area of each plot was 2m2 (2m length x 1m width) and spacing between each plant was 25cm and each plot was 1m. The experimental design was a Randomized Complete Block Design (RCBD) involved five treatments and four replications. The treatments were T0: Control (no fertilizer), T1: Cattle manure only, T2: Cattle manure + Urea + NPK (15:15:15), T3: Cattle manure + Liquid organic fertilizer and T4: Cattle manure + Urea + NPK + Liquid organic fertilizer. Though the experiment showed that the application of cow manure, urea and NPK fertilizer (T2) had gave plants with the greatest plant height, leaf area (length and width), root length, root weight, plant weight and biomass yield of celery. The data obtained from these treatments were significantly higher than the data obtained from the control (T0) and cattle manure alone (T1). Therefore, it is concluded that the use of organic manure from cattle manure in the production of vegetables like celery cabbage should be combination with appropriate inorganic fertilizer.